The European fiscal reform and the plight of the Euro - Mundell, Robert (Economics and Business Review, 2011)
The paper presents the background of the American crisis in 2007-2008 that later spread into the global crisis. It distinguishes and discusses four phases of the crisis: subprime mortgage crisis, soaring dollar and the Lehman Brothers fiasco, US and global recession, and, finally, European debt crisis. In the above context, the benefits and costs of joining the Eurozone are presented, particularly from the Polish perspective. The need of fiscal reforms and concerns regarding Eurozone institutions are addressed. The paper has been prepared based on the Keynote Speech by Robert Mundell during the 17th Global Finance Conference held in Poznan, Poland in June 2010. The Speech presented here was made possible in part by support from the Polish Financial Supervision Authority. (original abstract)